2022
DOI: 10.1097/md.0000000000031945
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ai-assisted colonoscopy on adenoma miss rate/adenoma detection rate: A protocol for systematic review and meta-analysis

Abstract: Background: Colonoscopy can detect colorectal adenomas and reduce the incidence of colorectal cancer, but there are still many missing diagnoses. Artificial intelligence-assisted colonoscopy (AIAC) can effectively reduce the rate of missed diagnosis and improve the detection rate of adenoma, but its clinical application is still unclear. This systematic review and meta-analysis assessed the adenoma missed detection rate (AMR) and the adenoma detection rate (ADR) by artificial colonoscopy. Methods: Conduct a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Advancements in artificial intelligence technology over the past decade have opened up new possibilities for overcoming human error during colonoscopy procedures [6]. Recent metaanalyses provide abundant evidence demonstrating the value of a computer-aided polyp detection (CADe) system by increasing the ADR and reducing missed adenomas [7,8,9,10]. Despite the impressive results, many studies have been criticized for having a low baseline ADR, raising the question of whether similar results would have been obtained had the baseline ADR been higher [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancements in artificial intelligence technology over the past decade have opened up new possibilities for overcoming human error during colonoscopy procedures [6]. Recent metaanalyses provide abundant evidence demonstrating the value of a computer-aided polyp detection (CADe) system by increasing the ADR and reducing missed adenomas [7,8,9,10]. Despite the impressive results, many studies have been criticized for having a low baseline ADR, raising the question of whether similar results would have been obtained had the baseline ADR been higher [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent metaanalyses provide abundant evidence demonstrating the value of a computer-aided polyp detection (CADe) system by increasing the ADR and reducing missed adenomas [7,8,9,10]. Despite the impressive results, many studies have been criticized for having a low baseline ADR, raising the question of whether similar results would have been obtained had the baseline ADR been higher [6,7,8,9]. Furthermore, previous meta-analyses concluded that CADe could aid in detecting only diminutive polyps while not increasing the detection of advanced adenoma [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…They all show a more or less significant increase in detection of small adenomas. The same results are summarized over and over again in no less than 16 meta-analyses [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], plus a protocol for a further one [36], as well as a meta-analysis of some of these meta-analyses [37]! "The question relates to the ultimate clinical relevance of increasing ADR from high to even higher levels …, we still do not know whether we have a cutoff ADR level, above which there is no further improvement in cancer prevention.…”
mentioning
confidence: 97%